Measuring oral health during pregnancy: sensitivity and specificity of a maternal oral screening (MOS) tool. Issue 1 (December 2016) - George, Ajesh; Dahlen, Hannah; Blinkhorn, Anthony; Ajwani, Shilpi; Bhole, Sameer; Ellis, Sharon; Yeo, Anthony; Elcombe, Emma; Sadozai, Ayesha; Johnson, Maree
Abstract Background Midwives can play a key role in promoting the oral health of pregnant women and assessing their oral health status. A maternal oral assessment tool (MOS) was developed and pilot tested by the study investigators to assist midwives in this role and the results were promising. The aim of this study was to undertake further sensitivity and specificity assessment of the MOS tool using two-comparison approaches- the longer oral health screening tool known as the Oral Health Impact Profile (OHIP-14) and an oral assessment by trained study dentists. Methods Pregnant women were recruited for this study as part of a larger randomised controlled trial of a Midwifery Initiated Oral Health (MIOH) program. Pregnant women completed the MOS and OHIP-14 as part of their initial assessment undertaken by 38 trained and accredited midwives. A dental assessment was conducted for all women in the intervention group using three trained study dentists with high inter rater reliability. Results Two hundred and eleven pregnant women participated in the validation of the MOS tool. Results from both approaches found the MOS tool to have high sensitivity, correctly identifying 88–94 % of women at risk of poor dental health, and low specificity (14–21 %). Conclusions This study has shown that the MOS tool can be successfully implemented by midwives during a woman's first antenatal visit and can identify up to 94 % of women at risk of poor oral health and needing a dental referral. The tool has the potential to be transferable to other antenatal care providers and could be incorporated into hospital obstetric database systems. Trial registration number ACTRN12612001271897, 6th Dec 2012, retrospectively registered.